Development of single filament testing procedure for polyacrylonitrile precursor and polyacrylonitrile-based carbon fibers. (August 2015) - Lyons, Kevin M; Newcomb, Bradley A; McDonald, Kenneth J; Chae, Han Gi; Kumar, Satish
Single filament testing protocols for polyacrylonitrile precursor and polyacrylonitrile-based carbon fibers have been developed to ensure reliable tensile results that can be compared to the standard testing protocols used by the industry. Accurate carbon fiber linear density measurement by vibroscope was quite sensitive to the pre-stress applied to the fiber. Gauge length dependence testing of the commercial carbon fibers exhibited that tensile strengths obtained at 25.4 mm gauge length are comparable to those reported by the manufacturer using the standard strand testing results. On the other hand, experimental carbon fibers that have not been surface treated or sized, showed that single filament tensile strength values at 6 mm gauge length was comparable to the strand testing results. In addition, the compliance corrected tensile moduli of carbon fibers obtained by single filament tests were also comparable to the moduli obtained from the standard strand testing results. A modified Weibull analysis, which accounts for sample volume effects, has also been used to determine the Weibull modulus of both the commercial and experimental carbon fibers.